2019
DOI: 10.1055/s-0039-1694723
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Thrombosis in Microsurgical Anastomoses: The Use of Intraoperative Pure Intraluminal Unfractionated Heparin

Abstract: Background Unfractionated heparin has anticoagulant properties by catalyzing antithrombin III, which inactivates coagulation enzymes. Used in microsurgery, it would prevent the occurrence of thrombosis during microsurgical anastomoses. The objective of this study was to evaluate the role of intraoperative irrigation of the vascular lumen with pure sodium heparin to prevent vascular thrombosis after end-to-end microsurgical anastomoses. Methods End-to-end anastomoses were performed on rats by 21 ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…[28][29][30] Ramelli et al showed that intraluminal application of heparin reduced the rate of thrombosis. 9 However, neither ASA nor the choice of thrombosis prophylaxis showed to prevent flap failure. Some studies even revealed a higher complication rate [31][32][33] since all systemic applied anticoagulatory substances have side effects, for example bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] Ramelli et al showed that intraluminal application of heparin reduced the rate of thrombosis. 9 However, neither ASA nor the choice of thrombosis prophylaxis showed to prevent flap failure. Some studies even revealed a higher complication rate [31][32][33] since all systemic applied anticoagulatory substances have side effects, for example bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…8 The intraluminal application of heparin has also shown to reduce the thrombosis rate of anastomoses in an animal study. 9 Pérez et al 10 reported that local subcutaneous injection of heparin to be an effective alternative in improving flap venous congestion. Topically administered heparin is used in the treatment of thrombophlebitis and for faster resorption of hematomas in sports medicine.…”
mentioning
confidence: 99%
“…The primary endpoint was vascular 60 min thrombosis. The results showed a significant impact with a decrease in the thrombosis rate of 2.6 with heparin irrigation without increasing complications [72].…”
Section: Prospective Cohort Studies/randomized-controlled Trials (1) ...mentioning
confidence: 85%
“…3,4 In reconstruction after head and neck cancer resection, elderly patients and those who received preoperative irradiation tend to have more postoperative complications. 5,6 The use of heparin 7 or papaverine 8 during reconstruction has been reported to prevent intraoperative thrombus formation at the anastomotic site. In the present study, moisturization during cancer resection was found to significantly reduce intraoperative arterial thrombosis.…”
Section: Discussionmentioning
confidence: 99%